2010
DOI: 10.1016/j.juro.2009.10.006
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Hormonal Therapy on Intermediate Risk Prostate Cancer Treated With Combination Brachytherapy and External Beam Irradiation

Abstract: We addressed the relative importance of radiation dose vs hormonal therapy for intermediate risk prostate cancer. With high biologically effective dose combination treatment androgen suppressive therapy did not have a significant impact on the 8-year biochemical failure-free rate. We question its routine use in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
3
12
1
Order By: Relevance
“…In addition, the detrimental effects on potency and quality of life are factors which are often crucial to younger men in treatment selection. In this analysis, the use of HT was not predictive of DFS in univariate analysis, in keeping with that of numerous reports in the literature showing lack of benefit of HT when combined with an optimal implant (17,(28)(29)(30). Unlike the study by Beyer et al (30), we did not see a detriment to overall survival with the use of HT, but our population was more than a decade younger.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the detrimental effects on potency and quality of life are factors which are often crucial to younger men in treatment selection. In this analysis, the use of HT was not predictive of DFS in univariate analysis, in keeping with that of numerous reports in the literature showing lack of benefit of HT when combined with an optimal implant (17,(28)(29)(30). Unlike the study by Beyer et al (30), we did not see a detriment to overall survival with the use of HT, but our population was more than a decade younger.…”
Section: Discussionsupporting
confidence: 88%
“…Several investigators have reported that neoadjuvant and continued adjuvant hormone therapy did not have significant impacts on the BRFR in patients receiving a high-dose implant with intermediate-risk prostate cancer [5,19]. In our study, the benefit of neoadjuvant CAB was only seen for low-dose implants (D90 <180 Gy), not at higher doses (D90 ≥180 Gy) in patients with intermediate-risk prostate cancer, as previously reported [7].…”
Section: Discussionsupporting
confidence: 85%
“…Some retrospective series have shown that prostate BT with additional ADT in intermediate to high risk patients is associated with a lower rate of bNED compared to those with BT alone [1,41,42]. Others however, have either found no benefit with the use of ADT, or a detrimental effect on overall survival [43][44][45]. The numbers of patients treated with ADT in our study are small but no convincing association could be shown between bNED and the use of ADT.…”
Section: Discussioncontrasting
confidence: 68%